PENERAPAN METODE MAUT, COPRAS DAN EDAS DALAM PEMILIHAN MEDIA PEMBELAJARAN ONLINE DI MASA PANDEMIC COVID-19 - Andreas Gerhard Simorangkir; Fatiyah Saidah; Mesran Mesran (Jurnal Teknologi Informasi Mura, 2022)
The Covid-19 pandemic period is a time when all conditions are not as usual for all people, including the world of education. In order for education to continue to run well, an online learning media is needed. Online learning media is media that is equipped with a controller that can be operated by the user so that the user can control and access what the user needs, such as downloading or uploading material. The lecturers usually do online learning only through online media, namely Google Classroom, even though there are several online media that can be done for online learning, such as WhatsApp, Zoom Meeting, Google Meeting and Moodle so that learning can still run well. In order to help the lecturers in the selection of learning media, a decision support system is needed. The method applied in this research is the MAUT, COPRAS and EDAS methods. In the application of these three methods, it is expected to be able to produce the best alternative. As for the results of the research on the Selection of Online Learning Media in the Covid-19 Pandemic Period, the best alternative produced is the online learning media "WhatsApp" with the MAUT method calculation with a value of Ui = 0.9273, the calculation of the COPRAS method with a value of Ui = 100% and calculation of EDAS method with ASI value = 0.165